A very compact internal WLAN antenna. Issue 9 (30th May 2019) - Wang, Hanyang; Ying, Lijun
Abstract: A very compact wireless local area network (WLAN) antenna is presented for the design of hand‐held mobile devices. The antenna does not need metal clearance underneath the antenna and it has very low profile. Both simulated and measured results show that the antennas with very small antenna volume and height can operate as a triple‐band WLAN antenna with good bandwidth and radiation efficiency.